2009
DOI: 10.1002/masy.200950703
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(vinyl acetate)‐block‐poly(dimethylsiloxane)‐block‐poly(vinyl acetate) Copolymers by Iodine Transfer Photopolymerization in Miniemulsion

Abstract: Summary: Iodine transfer polymerization of vinyl acetate in aqueous miniemulsion, initiated by UV radiation in the presence of an α,ω‐diiodo‐poly(dimethylsiloxane) macrophotoiniferter has been performed. The formation of a triblock copolymer latex PVAc‐b‐PDMS‐b‐PVAc has been evidenced by 1H‐NMR and size exclusion chromatography. The size of the PDMS and PVAc blocks were modulated thus opening the way to a wide range of copolymers with different properties. A detailed study of the reaction mechanism showed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…[ 12 ] Although the vast majority of these polymerizations are thermally initiated, an alternative approach was UV light induced the polymerization from monomer microemulsion. [13][14][15][16] More recently miniemulsions [17][18][19] composed of metastable acrylate nanodroplets ( < 100 nm) with weakly scattering properties are prepared in water permitting a suffi cient penetration of light. Nucleation is assumed to take place inside nanodroplets and promote their conversion into polymer particles, in the absence of any destabilization phenomena.…”
Section: Photopolymerization In a Photoreactormentioning
confidence: 99%
“…[ 12 ] Although the vast majority of these polymerizations are thermally initiated, an alternative approach was UV light induced the polymerization from monomer microemulsion. [13][14][15][16] More recently miniemulsions [17][18][19] composed of metastable acrylate nanodroplets ( < 100 nm) with weakly scattering properties are prepared in water permitting a suffi cient penetration of light. Nucleation is assumed to take place inside nanodroplets and promote their conversion into polymer particles, in the absence of any destabilization phenomena.…”
Section: Photopolymerization In a Photoreactormentioning
confidence: 99%
“…The main drawback of conventional (macro)emulsions is a strongly attenuated light penetration, resulting generally in very poor photoinitiation rates. Consequently, several authors have suggested that less scattering nano­emulsions such as miniemulsions (50–500 nm) may serve as a better platform for future developments in the domain of photopolymerization . For example, Jasinski et al recently combined several spectrophotometric methods to extract absorption ( K λ ) and scattering ( S λ ) coefficients from acrylate miniemulsions.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, nucleation takes place preferentially in the monomer droplets, making miniemulsion amenable to many unconventional applications including water‐sensitive reactions (ionic, catalytic, step‐reaction polymerizations), controlled radical polymerizations, encapsulation of liquids, preformed polymers, or inorganic particles, and many others . Recently, several examples of photoinitiated miniemulsion polymerizations driven by UV light have been very successful . The key feature here is the smaller size of the miniemulsion droplets (40–500 nm) compared with macroemulsion systems (500 nm–50 µm), leading to a better light penetration and an optimized absorption/scattering ratio.…”
Section: Introductionmentioning
confidence: 99%